Internalizing the Value of Religious Moderation for Generation Z in Facing the Challenges of Plurality - Moh Restu Hoeruman; Achmad Fadil; Agnes Fransiska Dewi; Nurul Fauziah; Khoirunnisa Khoirunnisa; Andi Nurindah Sari; Mustapa Ahmad (Yayasan Zia Salsabila, 2025)
Generation Z lives in a social space characterized by openness of information, cross-cultural interactions, and high intensity of digital media use. These conditions present both opportunities and challenges, especially in relation to their ability to respond to religious, cultural, and identity plurality. This study aims to analyze the process of internalizing religious moderation values among Generation Z and effective strategies that can be applied in the context of education, particularly Islamic Religious Education. The research method used is a descriptive qualitative approach through literature study and limited interviews with students to explore perceptions, attitudes, and practices of religious moderation. The results of the study indicate that the internalization of religious moderation values can be optimized through three aspects: strengthening digital religious literacy, collaborative learning that emphasizes dialogue across differences, and the exemplary role of educators in applying the principles of tawassuth, tasamuh, tawazun, and i'tidal. The conclusion of this study confirms that religious moderation is an important competency for Generation Z in building inclusive attitudes and adaptive abilities to face socio-religious diversity in the contemporary era.